Peningkatan Motivasi Belajar dan Daya Serap Menggunakan Media Interactive Board pada Peserta Didik di Kelas X SMK Jetis 1 Ponorogo - Sari, Nia Yunia; Zahroh, Muflikhatus Sholihah; Khoirunisa, Ifa (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2020)
This paper was prepared with the aim of knowing the effectiveness of using Interactive Board media to increase learning motivation in class X Ak students of SMK Jetis 1 Ponorogo for the 2019/2020 Academic Year, totaling 12 students. This research is a Classroom Action Research (CAR) which consists of two cycles with each cycle consisting of four stages, namely the first stage is Planning (planning), the second stage is acting (implementing), observing (observing) and the fourth stage is reflecting (reflecting), where the teacher is the executor of learning while the researcher is the observer. This research was conducted in the odd semester of the 2019/2020 academic year, from November to December. The subjects of this study were students of class X Ak. which consisted of 12 students. The object of research is the motivation and absorption of students. Data collection techniques using observation and interviews. Research data obtained during action research until the final assessment of the action. The results showed that the results of the initial test after the action in the first cycle of 12 students there were 5 students (41.66%) experienced an increase, while in the second cycle the number of students who increased by 11 students (91.66%). Thus the use of interactive board media in PAI subjects can increase the learning motivation of class X Ak SMK Jetis 1 Ponorogo students.